2016
DOI: 10.1128/aem.00508-16
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnetic Recovery and Bioaccumulation of Selenium Granules in Magnetotactic Bacteria

Abstract: Using microorganisms to remove waste and/or neutralize pollutants from contaminated water is attracting much attention due to the environmentally friendly nature of this methodology. However, cell recovery remains a bottleneck and a considerable challenge for the development of this process. Magnetotactic bacteria are a unique group of organisms that can be manipulated by an external magnetic field due to the presence of biogenic magnetite crystals formed within their cells. In this study, we demonstrated an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
(33 reference statements)
0
30
0
Order By: Relevance
“…Since the early 1980s, A. cornea has been artificially cultivated in China, and its social demands have recently increased greatly owing to its obvious advantages. Like other edible mushrooms, temperature, enzyme and microbiota greatly influence A. cornea during growth, which could lead to changes in polysaccharide and microelements in the sporocarp [ 10 , 11 ]. Among all factors that influence the growth of A. cornea , temperature has the greatest effect and can determine the output and quality of A. cornea .…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1980s, A. cornea has been artificially cultivated in China, and its social demands have recently increased greatly owing to its obvious advantages. Like other edible mushrooms, temperature, enzyme and microbiota greatly influence A. cornea during growth, which could lead to changes in polysaccharide and microelements in the sporocarp [ 10 , 11 ]. Among all factors that influence the growth of A. cornea , temperature has the greatest effect and can determine the output and quality of A. cornea .…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of another transition metal in magnetosome magnetite modified the magnetic properties of the crystals and could therefore lead to the design of new biomaterials with specific, possibly tailor-made magnetic properties. Based on the absorption and immobilization of metals from culture medium and the fact that MTB can be magnetically removed from sediment and water, the use of these microorganisms in bioremediation has been proposed by several investigators [ 84 , 85 , 86 , 87 ]. Tanaka and colleagues [ 84 ] showed that cells of Ms. magneticum AMB-1 are relatively resistant to tellurium and able to concentrate and crystallize this element in structures different from magnetosomes within the cell.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic concentration and recovery of cells of Ms. magneticum strain AMB-1 exposed to Cd resulted in significant removal of Cd from the growth medium when tested in vitro using a genetically modified strain of the organism that had several hexahistidine residues exposed on the cell surface [ 109 ]. In the in vitro evaluation of magnetic recovery of Se using cells of Ms. magneticum strain AMB-1 grown in culture medium containing SeO 3 2− , cells were able to reduce SeO 3 2− to Se, accumulating the element in intracytoplasmic granules not associated with magnetosome synthesis ( Figure 6 ) [ 85 ]. After the magnetic recovery of cells, 68.1% of the Se was removed from the medium ( Figure 6 ) [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…As MTB are able to store iron, a coculture of MTB may reveal their ecological dynamics with other micro-organisms, especially in iron cycling. Additionally, the ability of MTB to take up toxic, heavy metals such as cobalt and manganese from their natural habitats [61] has intriguing future implications for using MTB as tools for ecological waste water treatment or heavy metal removal.…”
Section: Bacterial Ecosystemsmentioning
confidence: 99%